THE EFFECT OF NON-PERFORMING LOANS ON BANK LIQUIDITY DURING THE COVID-19 PANDEMIC - Christanto, Felicia; Susanto, Grace Febiola (Universitas Nusa Cendana, 2024)
This study aims to determine the impact of the Covid-19 pandemic on banking liquidity in Indonesia. This study used data samples from 25 banks in Indonesia listed on the stock exchange from 2016 Q1 – 2021 Q4. Data collection for 6 years was chosen to determine banking trends before and during the pandemic. The research method used was regression panel data using the independent variable non-performing loan ratio and the dependent variable loan-to-deposit ratio to measure bank liquidity. The period before the COVID-19 pandemic (2016 Q1 - 2020 Q1) and after the COVID-19 pandemic (2020 Q2 - 2021 Q4) used dummy variables. The result was that the ratio of non-performing loans affected bank liquidity during the COVID-19 pandemic. This is due to the disruption of bank cash inflow because many debtors have difficulty fulfilling obligations to the bank. Keywords: Banking Liquidity; Credit Risk; Non-Performing Loans